Commodities and the South African investment portfolio - Rodrigues, Jason Ross (My University, 2014)
This study aims to make a contribution to the better understanding of the role commodities play in a portfolio, specifically in a South African investment portfolio. It considers the interactions between a fully collateralised commodity index and South African equities, bonds, property and cash. The study uses historical data to asses if commodities provide addition benefits to an investment portfolio, namely, additional returns, diversification and as an inflation hedge. The analyses used in this study are performance analysis, correlation studies and portfolio optimisation. Based on the evidence presented in this study we show that there were some benefits to adding commodities to a South African investment portfolio, namely, using commodities to diversify a portfolio and as an inflation hedge. However, commodities did not provide sufficiently large enough returns to justify their high volatility and as such would not be an appropriate stand alone investment in the South African context.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Commodities; Investments; Portfolio management; South Africa